Balur and Improving Quality of Life - Jayanti, Gatra Ervi; Subagjo, Saraswati (Journal of Tropical Life Science, 2016)
Balur treatment aimed to leach free radicals overwhelmingly produced in unhealthy body with rubbed over the human body. In Balur used some amino acid and herbal such as Bawang Sabrang (Eleutherine palmifolia (L.) Merr), Kopi Balur (Mixed Coffea arabica L. with Acetosal), Coconut Water (Cocos nucifera L.), Secang (Caesalpinia sappan L.) and â€œDivineâ€ smoke from cloves (Syzygium aromaticum (L.) Merr. & L. M. Perry) and Tobacco (Nicotiana tabacum L). This is an observation research of Balur application in volunteers during four years at Rumah Sehat, Malang, Indonesia. The result suggested that Balur can improve quality of life Â in male volunteers i.e. 61,54% for Cancer (39 volunteers); 80% for Tumor (20 volunteers); 86,36% for Diabetes mellitus (22 volunteers); 93,33% for Heart (15 volunteers); 92,86% for Autism (28 volunteers); 72,73% for Hepatitis (11 volunteers); 100% neuron disease for (2 volunteers); 93,62% for various of disease (94 volunteers). Moreover imrovement quality of life in female volunteers i.e. 72,31% for Cancer (65 volunteers); 88,57% for Tumor (35 volunteers); 75% for Diabetes mellitus (16 volunteers); 100% for Hemorrhoid (3 volunteers); 100% for stroke (3 volunteers); 40% for Cardiomegaly (5 volunteers); 66,67% for Autism (3 volunteers); 88% for various of disease (50 volunteers) and 100% for healthy (3 volunteers).Â Keywords: Balur, herb in Balur process, improving quality of life